The Antioxidant Activity of Pagoda Flower (Clerodendrum paniculatum L.) Ethanol Extract using Visible Spectrophotometric Method - Hafiz, Ihsanul; Ginting, Mandike; Yuermaileni, Yuermaileni (Indonesian Journal of Pharmaceutical and Clinical Research, 2019)
Abstract. Pagoda flower is one of the plant species included in the genus Clerodendrum which has a number of different species of 580 species, and is spread evenly in Asia, Africa, America, and Australia. A number of species of this genus have been used in traditional medicine in Asia and Africa. India, China, Korea, Thailand and Japan. The antioxidant activity of this plant is known to be very strong, so in this article the antioxidant activity of the flower part of the Clerodendrum paniculatum L. species will be described. The ability of antioxidant activity was measured by the DPPH method (1,1-diphenyl-2-picrylhydrazyl) which was measured using a Visible spectrophotometer using Vit C as a comparison. The results showed that the ethanol extract of pagoda flowers has antioxidant activity with an IC50 value of 64.889 ppm (strong). The Vit C comparison has an IC50 value of 8.539 ppm (very strong). Keyword: Antioxidant, Clerodendrum Paniculatum L., Visible Spectrophotometric. Abstrak. Bunga Pagoda merupakan salah satu spesies tanaman yang termasuk dalam genus Clerodendrum yang memiliki jumlah spesies yang berbeda sejumlah 580 spesies, dan tersebar merata di Asia, Afrika, Amerika, dan Australia. Sejumlah spesies dari genus ini telah digunakan dalam pengobatan tradisional di kawasan Asia dan Afrika. India, China, Korea, Thailand, dan Jepang. Aktivitas antioksidan dari tanaman ini diketahui sangat kuat, sehingga dalam artikel ini akan dipaparkan aktivitas antioksidan yang dimiliki oleh ekstrak etanol bagian bunga dari spesies Clerodendrum paniculatum L. Pengujian aktivitas antioksidanya dilakukan dengan metode DPPH (1,1-diphenyl-2-picrylhydrazyl) yang diukur menggunakan spektrofotometer Visibel dengan menggunakan Vit C sebagai pembanding. Hasil penelitian menjukkan bahwa ekstrak etanol bunga pagoda memiliki aktivitas antioksidan dengan nilai IC50 sebesar 64,898 ppm (kuat). Pembanding Vit C memiliki nilai IC50 sebesar 8,539 ppm (sangat kuat). Kata Kunci: Antioksidan, Clerodendrum paniculatum L., DPPH, Spektrofotometri Vis.